Measuring Energy Efficiency: Accounting for the Hidden Costs of Product Failure - Fraas, Art; Miller, Sofie E. (Economics of energy & environmental policy, 2020)
Several recent studies suggest that minimum energy efficiency standards for appliances have resulted in higher-quality products with little or no increase in price. We have conducted case studies for the two major household appliances—clothes washers and refrigerators—subject to Department of Energy (DOE) energy efficiency standards implemented over the 2001 to 2011 period. We identify three issues plaguing appliances that yielded lower cost savings than projected in DOE's ex ante analyses: (1) product life and reliability; (2) greater energy usage than anticipated; and (3) additional operation and maintenance costs. These two case studies illustrate the need to consider the potentially substantial costs of operation and repair in conducting retrospective analyses of DOE energy efficiency standards. In addition, these case studies identify the limited information available to consumers on repair and replacement rates at the time of purchase and suggest some possible policy responses.